「『婦人文藝』解説・総目次・索引」より - 黒澤亜里子; Kurosawa, Ariko (不二出版, 1987)
Tables of contents and author-name index for the 10-volume set Fujin bungei.
Digitized material from "'Fujin bungei' kaisetsu, sōmokuji, sakuin"
Keywords: Fujin bungei -- Indexes; Japanese literature -- Women authors -- Periodicals -- Indexes; Japanese literature -- 20th century -- Periodicals -- Indexes; Fujin bungei; Japanese literature -- Periodicals; Japanese literature -- Women authors -- Periodicals